Frontispiece: On‐demand field shaping for enhanced magnetic resonance imaging using an ultrathin reconfigurable metasurface (View 3/2021). Issue 3 (17th June 2021) - Wang, Hanwei; Huang, Hsuan‐Kai; Chen, Yun‐Sheng; Zhao, Yang
Abstract : In article number 20200099, Hanwei Wang and co‐workers have proposed a theoritical design of an ultrathin reconfigurable metasurface to enhance the signal‐to‐noise ratio of magnetic resonance imaging. The enhancement can target a specific region in the imaging plane with any desired shapes while minimumly disrupt the spin‐excitation to maintain a high imaging quality. In this cover, the spins pointing up illustrate the uniform excitation of protons of an imaging object. The different shapes of the component forming the metasurface create a strong coupling with the protons in a specific region, where the signals are selectively enhanced. The selected enhancement region in this cover is designed to form the shapes of "U" and "I" representing the University of Illinois.